PERTANGGUNGJAWABAN PT. HEROTAMA INDONUSA CABANG SUMATERA BARAT DALAM PELANGGARAN KONTRAK KERJA DENGAN KILANG PANASONIC SYSTEM NETWORKS - Gladysha Indahcantika Mazalio; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The concept of the rule of law provides rights and obligations to citizens by the state, one of which is guaranteed by the state is the availability of employment for citizens. This can be seen in Article 28 D Paragraph 2 of the 1945 Constitution which states that everyone has the right to work and to receive fair and appropriate compensation and treatment in an employment relationship. Judging from this article, it states that the state must contribute to guarantee citizens for decent work. To support government policies and programs, the government issues government policies and programs in the placement of Indonesian migrant workers abroad.However, in its implementation a lot of legal violations occurred concerning Indonesian Migrant Workers working abroad, such as violating the law in a work agreement or (default). There are many incidents where Indonesian Migrant Workers who flee while doing work cause many service providers to become victims of losses for mistakes made by Indonesian Migrant Workers.The purpose of writing this thesis, namely; First, knowing the responsibility of PT.Herotama Indonusa for migrant workers who have violated the employment contract with the Panasonic refinery, Second; know the nature of the legal consequences of Indonesian Migrant Workers who violate employment contracts.From the results of the study based on two problem formulations can be concluded, First, In the responsibilities carried out by the company PT. Herotama Indonusa to the Panasonic Refinery, PT. Herotama Indonusa must compensate for actions committed by migrant workers. PT. Herotama also had consequences on the blacklist from the refinery so that this was very detrimental to PT. Herotama Indonusa. Second, the implementation of the legal consequences given to the Migrant Workers should be to impose sanctions in accordance with the contents of the employment contract agreement between the Migrant Worker and PT.Herotama Indonusa Company, but in reality the Migrant Worker does not fulfill the contents of the agreement. And also supposedly in Law number 18 of 2017 concerning the Protection of Migrant Workers regulates the obligations of Migrant Workers when committing violations or mistakes related to work contracts.Keywords: Liability-violation-employment contract